2021
DOI: 10.1002/gch2.202100087
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Multiscale Fog Collector Inspired by Sarracenia Trichome Hierarchical Structure

Abstract: normally tend to condense on the protruding solid surface, but the already condensed bulked water film will slow down further condensation. [6][7][8] In nature, many biological samples have developed unique parts to solve the bulked water film-restrained fog condensation, [9][10][11] such as spider silk with spindle-knots [12][13][14] and cactus with cone spines. [15][16][17] Their conical structures can directionally transport condensed water from the tip to the bottom, releasing the tip surface area for furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…For rough solid surfaces, the deposited liquid droplets exhibit three kinds of classic wetting models: the Wenzel state, Cassie–Baxter state, and hemiwicking state, which are determined by the surface structure and interfacial interactions of liquids and solids. In the hemiwicking state, the fluid spontaneously imbibes or wicks along the narrow micro-/nanostructured roughness ahead of the fluid droplet under the balance of the capillary force and the viscous force, like wicking behaviors. In recent years, the wicking phenomenon, including wicking and hemiwicking, has attracted increasing attention for its significance in engineering applications, such as thermal management, water harvesting, fuel cells, microfluidics, and biosciences, in which the wicking behavior determined by micro-/nanostructures plays a critical role in the process of liquid transportation. The mechanism of the wicking process is rather complex, mainly involved in the competition of the drive of the capillary force and the hindering of the viscous force, both of which favor smaller length scales.…”
Section: Introductionmentioning
confidence: 99%
“…For rough solid surfaces, the deposited liquid droplets exhibit three kinds of classic wetting models: the Wenzel state, Cassie–Baxter state, and hemiwicking state, which are determined by the surface structure and interfacial interactions of liquids and solids. In the hemiwicking state, the fluid spontaneously imbibes or wicks along the narrow micro-/nanostructured roughness ahead of the fluid droplet under the balance of the capillary force and the viscous force, like wicking behaviors. In recent years, the wicking phenomenon, including wicking and hemiwicking, has attracted increasing attention for its significance in engineering applications, such as thermal management, water harvesting, fuel cells, microfluidics, and biosciences, in which the wicking behavior determined by micro-/nanostructures plays a critical role in the process of liquid transportation. The mechanism of the wicking process is rather complex, mainly involved in the competition of the drive of the capillary force and the hindering of the viscous force, both of which favor smaller length scales.…”
Section: Introductionmentioning
confidence: 99%
“…The ultrafast liquid transport has been found on the Sarracenia trichome, and its unique HMC with high–low ribs has also been proved to play a great role in fog capture and harvesting. , In order to reveal the influence of different HMCs, the needles with N high ribs and n low ribs are set under the same saturated fog flow of 0.35 m/s. Fluorescent particles were doped in saturated fog and activated by ultraviolet light to better observe the fog harvest process.…”
Section: Resultsmentioning
confidence: 99%
“…The artificial trichome can harvest fog ultrafast and transfer water against gravity like the genuine Sarracenia trichome. 108 Wang et al 106 reported a subulate Cu sheet with Sarracenia-like multilevel microchannels and cactus spines developed by pulsed laser direct structuring for continuous and high-performance water collection (Figure 9f). This unique combined structure (a spine with barbs and hierarchical channels) presented the highest fog harvesting speed (513 μg s −1 ) compared to the hierarchical channels (315 μg s −1 ), the spine with barbs and grooves (340 μg s −1 ), and the spine with barbs (377 μg s −1 ).…”
Section: Sarracenia Trichomes and Its Bioinspired Materialsmentioning
confidence: 99%
“…The major channels were constructed by an inner gear pattern, while the junior microchannels were automatically generated because of the assembly of glass fiber monofilaments. The artificial trichome can harvest fog ultrafast and transfer water against gravity like the genuine Sarracenia trichome 108 . Wang et al 106 reported a subulate Cu sheet with Sarracenia ‐like multilevel microchannels and cactus spines developed by pulsed laser direct structuring for continuous and high‐performance water collection (Figure 9f).…”
Section: Water Transport Using Hydrophilic Surfacesmentioning
confidence: 99%